Perlindungan dan Penetapan Nasab Anak Diluar Nikah: Perspektif Fikih Islam - Sukma, Melati; Patimah, Patimah; Suhufi, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
This article discusses how to protect children outside of marriage from an Islamic jurisprudence perspective. This type of research is qualitative in nature and is carried out using the Library Research method, namely a method of analyzing, interpreting and classifying data obtained from various suitable sources. The results of this research are that protection for children outside of wedlock is only obtained through their mothers and their mothers' families. Because illegitimate children only have a lineage relationship with their mother, the protection they get from their father does not get protection because they don't have a lineage relationship. As illegitimate and illegitimate children, children born in this context do not receive protection for the right to livelihood, educational guardianship, inheritance and cannot be provided with services in state administration.